Interaction Analysis Based on Shapley Values and Extreme Gradient Boosting: A Realistic Simulation and Application to a Large Epidemiological Prospective Study - Orsini, Nicola; Moore, Alex; Wolk, Alicja (Frontiers in Nutrition, 2022)
Background: Shapley values (SHAP) based on tree-based machine learning methods have been proposed to interpret interactions between exposures in observational studies but their performance seldomly evaluated. Methods: Data from population-based cohorts in Sweden of 47,770 men and women with complete baseline information on diet and lifestyles were used to inform a realistic simulation in 3 scenarios of small (ORM=0.75 vs ORW=0.70), moderate (ORM=0.75 vs ORW=0.65), and large (ORM=0.75 vs ORW=0.60) discrepancies in the adjusted mortality odds ratios conferred by a healthy diet among men and among women. Estimates obtained with logistic regression (L-ORM; L-ORW) and SHAP values (S-ORM; S-ORW). Results: The sensitivities of detecting small, moderate, and large discrepancies were 28%, 83%, and 100%, respectively. The sensitivities of a positive sign (L-ORW>L-ORM) in the 3 scenarios were 93%, 100%, and 100%, respectively. Similarly, the sensitivities of a positive discrepancy based on SHAP values (S-ORW>S-ORM) were 86%, 99%, and 100%, respectively. Conclusions: In a realistic simulation study, the ability of the SHAP values to detect an interaction effect was proportional to its magnitude. At the contrary, the ability to identify the sign or direction of such interaction effect was very high in all the simulated scenarios.